Examination Reforms - Sinha, Sharad (SCHOOL SCIENCE, 2014)
Come the month of March and the temperature soars, so does the anxiety of students as examinations approach. This is followed by a mad rush to score more and more marks. This cycle is repeated every year. We have been brought up being told to study well, so that we score high in the examinations. The comparison among peers and their parents based on the examination marks is not only rampant in Indian society but throughout the world. The kids have been made to believe that the higher they score; higher are their prospects of getting employed. Education is often linked to employment and earning livelihood. The problem today is that the examination system has also become a victim of consumerism. The personality of the student is often valued less or more on the basis of the marks scored by him/her in the examination. The grim side of the examinations is that instead of being used as a pedagogic tool they are being used for elimination of people opting for higher jobs or higher education. This accelerates a mad race and unhealthy competition in order to get highest marks/grades from primary classes onwards.